KAJIAN INVESTASI PERAHU PENANGKAP IKAN DI PANTAI PAYANGAN WATU ULO DITINJAU DARI ANALISIS FINANSIAL DI JEMBER - Hamzah Fanzuri; Yani Dahliani (RELASI : JURNAL EKONOMI, 2014)
This research was intended to identify: (a) Investment of addition of 5 units of fishing boats in the area of Payangan Watu Ulo Beach with composition of total own capital which gives the most financially feasible results; (b) Investment of addition of 5 units of fishing boats in the area Payangan Watu Ulo Beach with the composition of 83.5% own capital and 16.5% financial leasing which gives fairly financially feasible results; (c) Investment of addition of 5 units of fishing boats in the area of Payangan Watu Ulo Beach with the composition of total capital financial lease that provides financially feasible results. (d) The level of effect of variable sensitivity on investment of addition of 5 units of fishing boats in Payangan Watu Ulo Beach.The method used in this research was descriptive-analytical method. Considering the area was quite narrow with limited population, the research applied total sampling/population/census techniques toward the research object. The determination of research location applied purposive sampling technique, the first sample collection and determination of the population used judgment sample technique, subsequent sampling used snowball sampling method. Analysis tools used in the research included the approaches of Pay Back Period (PBP), Net Present Value (NPV), Internal Rate Of Return (IRR), and Benefit Cost Ratio (B/C Ratio), Sensitivity Analysis and Rate On Investment (ROI).The research conclusions based on the results of data analysis of research are: (a) It was proved that the composition of own capital provided the most financially feasible result; (b) It was proved that the composition of mixed capital with the proportion of 83.5% own capital and 16.5 loan capital gave the fairly financially feasible result; (c) It was proved that the composition of the total loan capital was financially infeasible. (d) The parameters of variable sensitivity which significantly influenced included the variables of result (sales price), fuel costs, and the extra costs of labor and transportation.